Residents’ Perceptions of the Woodcraft Knowledge Transfer Program for the Development of a Reading Station at the People’s Housing Project (PPR) Kempas Permai, Johor - Mohd Ishar, Mohamad Izzuan; Aripin, Muhamad Afzamiman; Omar, Mohideen Kutty; Mohd Yusof, Siti Norbalkis (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study evaluates the effectiveness of a community-based woodcraft knowledge transfer program grounded in the Technical and Vocational Education and Training (TVET) approach to empower low-income urban communities at PPR Kempas Permai, Johor Bahru. The main objective was to assess participants’ improvements in knowledge, skills, and attitudes towards woodcraft and social responsibility through the collaborative construction of a Reading Station. A quantitative pre-test and post-test design was employed involving 11 participants comprising youth and community committee members. Data were collected using a five-point Likert scale questionnaire encompassing three key domains: basic woodcraft knowledge, understanding of work processes, and the overall impact of the workshop. Findings revealed significant improvements across all domains, with mean score increases ranging from +1.291 to +1.523, particularly in creativity, confidence, and awareness of safety practices. The results demonstrate that experiential learning aligned with TVET principles effectively enhanced participants’ technical competencies, social values, and sense of community ownership. Overall, the study underscores the potential of community-based TVET initiatives as a holistic development model that integrates skill empowerment, literacy enhancement, and social responsibility among low-income urban populations.
Keywords: TVET; knowledge transfer; woodcraft; community development; literacy; experiential learning